Knowledge, attitudes and practices about Cannabis light among a sample of Italian undergraduates - Marotta, Daniela; Borzì, Salvatore; Pozzoli, Angela; Vitale, Katia; Gazzanelli, Sergio; Vitali, Matteo; Protano, Carmela (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. Over the past few years, the market for “cannabis light”, substance with a tetrahydrocannabinol content of less than 0.6% (according to Italian law), has become established. The aim of the present study was to evaluate knowledge, attitudes and practices about cannabis light products among a sample of Italian undergraduates.Methods. This cross-sectional study was conducted in the academic year 2023/2024. Participants completed an anonymous questionnaire regarding socio-demographic data, knowledge about cannabis light products and their effects, attitudes and practices related to these products. Responses on knowledge were aggregated into a dichotomous variable (“good knowledge” and “poor knowledge”). A multivariate analysis was performed on the knowledge variable using age, gender, type of secondary school attended, tobacco use and having used cannabis light-containing products as independent variables.Results. Only 24.6% of the sample stated that they had used a product containing cannabis light at least once and 70.1% showed poor knowledge about such products. Students from technical or vocational secondary schools were significantly less likely to have good knowledge (OR=0.4; 95%CI=0.19-0.88). In contrast, those who had used these products at least once were more likely to have good knowledge (OR=4.8; 95%CI=2.84-8.25).Conclusions. Despite the increasing popularity of cannabis light products, the level of knowledge among university students remains low. Therefore, interventions are needed to fill knowledge gaps about these products and to guarantee their informed use.